Silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, and preparation method and application thereof
Patent Information
- Application Number
- CN202610729444.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-26
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2046-05-26
AI Technical Summary
[0005]为了解决目前现有水基钻井液添加剂存在的功能分散、热盐稳定性不足以及硅烷改性层易失效等问题,本发明提供一种无硅烷聚离子液体功能化纳米复合钻井液处理剂
[0024]本发明公开了以下技术效果:现有的水基钻井液处理剂在页岩地层应用中,普遍存在抑制性不足、封堵效果有限、润滑性差以及在高温高盐条件下稳定性不足等问题,难以满足深层及超深层复杂页岩井段的钻井需求。本发明提供了一种无硅烷聚离子液体功能化纳米复合钻井液处理剂,通过在无机纳米核表面引入稳定的膦酸类锚定层和无氟聚离子液体聚合物刷层,结合改性淀粉复合外壳,实现了页岩抑制、微纳封堵、润滑减摩与降滤失等多功能协同,显著改善了现有水基钻井液在深层页岩井中的应用性能。
Smart Images

Figure CN122278450B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oilfield chemistry technology in petroleum drilling engineering, and in particular to a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, its preparation method, and its application. Background Technology
[0002] Shale formations generally contain abundant clay minerals, have a dense structure, and are rich in microfractures and pores, making them extremely sensitive to drilling fluids. In shale drilling, the choice of drilling fluid system directly affects wellbore stability, rate of penetration (ROP), frictional torque, and cementing quality. Currently, oil-based drilling fluids, which are the most widely used, excel in inhibition, lubrication, and plugging properties, thus occupying a major share of the shale oil and gas drilling market. However, oil-based drilling fluids are expensive, pose significant environmental risks, have a relatively slow ROP, and poor compatibility with cementing mud, leading to potential problems in subsequent operations. In contrast, water-based drilling fluids have advantages such as low cost, environmental friendliness, fast ROP, and good compatibility with cementing systems, which aligns better with the development direction of green drilling. However, they are significantly lacking in inhibition, lubrication, and plugging properties, making it difficult to meet the comprehensive requirements of safe and efficient drilling in complex conditions such as shale formation hydration instability and high frictional torque in long horizontal sections.
[0003] To improve the performance of water-based drilling fluids, researchers have developed various functional materials, such as inorganic salts, organic amines, polyols, ionic liquids and their polymers, nanoparticles, and heat-resistant polymers. While these materials have achieved some improvement in individual properties such as inhibition, lubrication, or plugging, they still suffer from common shortcomings in practical applications: First, their functions are dispersed, often only improving one aspect and lacking multi-functional synergy; second, their thermosalt stability is limited, with many materials exhibiting significant performance degradation at high temperatures (above 200°C) and in high-concentration brine; third, particles or polymers are prone to agglomeration or degradation in high-salt and high-shear environments, leading to insufficient durability of plugging and lubrication. Therefore, existing water-based drilling fluids still struggle to simultaneously meet the comprehensive requirements of low expansion, low fluid loss, and low friction in deep, ultra-deep shale wells and long horizontal well sections.
[0004] To address this issue, some technologies have attempted to modify the surface of inorganic nanoparticles using silane coupling agents, followed by composites with ionic liquid segments to enhance dispersibility and interfacial bonding. However, silane modification has inherent limitations; its Si–O–M bonds are easily hydrolyzed under high-temperature, high-salt, or alkaline environments, leading to the gradual detachment of the surface modification layer and a decrease in the stability of the composite structure. Furthermore, the effectiveness of a single silane-ionic liquid modification layer in micro- and nano-pore throat sealing and wellbore lubrication is limited, making it difficult to form an integrated barrier that combines inhibition, sealing, and lubrication. Therefore, there is a need to develop a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent. Through more stable interfacial anchoring and multi-layered structural design, this agent can achieve synergistic effects of inhibition, sealing, and lubrication simultaneously under high-temperature and high-salt environments, thus providing more reliable technical support for the application of water-based drilling fluids in shale formations. Summary of the Invention
[0005] To address the problems of functional dispersion, insufficient thermosalinity, and easy failure of silane-modified layers in existing water-based drilling fluid additives, this invention provides a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent. This agent achieves more stable interfacial bonding and multifunctional synergistic effects through non-silane chemical anchoring and a core-shell gradient composite structure, enabling it to perform long-term functions such as shale suppression, micro-nano fracture sealing, and wellbore lubrication under high-temperature and high-salinity environments.
[0006] To achieve the above objectives, the present invention provides the following solution:
[0007] One of the technical solutions of this invention is a method for preparing a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, comprising the following steps:
[0008] Step 1: Disperse the nanonuclei in water to obtain a dispersion; add an anchoring agent to the dispersion to react and obtain intermediate product I;
[0009] Step 2: Add the fluorine-free anionic salt solution to the monomer solution to carry out the reaction, followed by displacement washing to obtain intermediate product II;
[0010] Step 3: Add intermediate product II, 2-acrylamide-2-methylpropanesulfonic acid, N-vinylpyrrolidone, polyethylene glycol methacrylate, lauryl methacrylate, and N-hydroxymethylacrylamide to the mixed solvent and mix well to obtain a monomer mixture; add intermediate product I to the monomer mixture, disperse evenly, and remove oxygen; then heat to 60-70℃ and add an initiator system to carry out a polymerization reaction; during the polymerization reaction, add modified starch solution for grafting and composite; after the polymerization reaction is completed, centrifuge and wash, and then spray dry to obtain the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent.
[0011] In a preferred embodiment of the present invention, in step one, the mass fraction of the nanonuclei in the dispersion is 5%~10%; the mass ratio of the nanonuclei to the anchoring agent is (5~10):(0.5-1.5); the temperature of the dispersion is 50~60℃; and the reaction conditions are set as follows: pH 3.0~4.0, reaction temperature 65~75℃, and reaction time 2~4h.
[0012] In a preferred embodiment of the present invention, in step one, the nanonucleus is at least one of nano-zirconium phosphate, nano-zirconium oxide, and UiO-66 (Zr); the particle size of the nanonucleus is 50~100nm; and the anchoring agent is at least one of vinylphosphonic acid, allylphosphonic acid, and 2-methacryloyloxyethylphosphonic acid.
[0013] In step one, after the reaction is completed, the process further includes centrifugation, washing, and dispersion with water until the solid content is 1wt%~3wt%.
[0014] In a preferred embodiment of the present invention, in step two, the concentration of the fluoride-free anionic salt solution is 0.8~1.0 mol / L, and the solvent is deionized water; the monomer solution is prepared by dissolving the polymerizable ionic liquid monomer in water; the molar ratio of the fluoride-free anionic salt to the polymerizable ionic liquid monomer is (1.05~1.20):1; the reaction conditions are set as follows: pH 6.0~7.5, reaction temperature not exceeding 40℃, reaction time 2~4h; the fluorine-free anionic salt is at least one of sodium lactate, sodium acetate, and sodium methanesulfonate; the polymerizable ionic liquid monomer is a mixture of methacryloyloxyethyltrimethylammonium chloride, N-vinylpyridine chloride, and 1-vinyl-3-methylimidazolium chloride in a molar ratio of (60-70):(15-20):(15-20); displacement washing is performed using a nanofiltration / tangential flow filtration system; the displacement washing conditions are set as follows: the displacement solution is a mixture of water / ethanol or water / isopropanol (ethanol or isopropanol volume fraction of 10~20%); operating temperature 20~30℃; transmembrane pressure difference 2~6 bar; tangential linear velocity 0.8~1.5 m / s; the displacement solution is continuously added using a constant volume displacement washing method until Cl - Content ≤0.05wt%.
[0015] In a preferred embodiment of the present invention, in step three, the amount of intermediate product II added is 40% to 70% of the mass of the mixed solvent, the amount of 2-acrylamide-2-methylpropanesulfonic acid added is 10% to 20% of the mass of the mixed solvent, the amount of N-vinylpyrrolidone added is 8% to 15% of the mass of the mixed solvent, the amount of polyethylene glycol methacrylate added is 4% to 8% of the mass of the mixed solvent, the amount of lauryl methacrylate added is 0.8% to 1.5% of the mass of the mixed solvent, and the amount of N-hydroxymethylacrylamide added is 0.05% to 0.2% of the mass of the mixed solvent; the amount of intermediate product I added is 10% to 30% of the mass of the mixed solvent.
[0016] The number average molecular weight of the polyethylene glycol methacrylate is 500-1500.
[0017] In a preferred embodiment of the present invention, the mixed solvent is a mixture of water and ethanol in a mass ratio of (90~95):(5~10); the initiation system is a mixture of potassium persulfate and sodium bisulfite in a mass ratio of (0.3~0.6):(0.05~0.15); the amount of the initiation system added is 0.35%~0.75% of the mass of the mixed solvent; the concentration of the modified starch solution is 5~20 g / L, the solvent is deionized water, and the modified starch is hydroxyethyl starch, hydroxypropyl starch, or starch hydroxypropyltrimethylammonium chloride; the amount of the modified starch solution added is 1%~5% of the mass of the mixed solvent.
[0018] In a preferred embodiment of the present invention, the conditions for the polymerization reaction are set as follows: reaction temperature 60~70℃, reaction time 4~6h; when the polymerization reaction has been going on for 3~4h, a modified starch solution is added for grafting and compounding.
[0019] In this invention, if the modified starch is added too early, it will cause the system to thicken prematurely and inhibit the polymerization reaction; if it is added too late, there will be insufficient grafting sites, and only a physical mixing layer will be formed, thereby reducing the grafting density and resulting in poor filtration performance.
[0020] In this invention, if the proportion of each raw material exceeds the range defined by this invention, whether too low or too high, the anchoring reaction will result in insufficient coverage or excessive deposition, leading to uneven anchoring layer, particle agglomeration, or decreased surface activity. This weakens the subsequent polymerization stability and core-shell bonding force, resulting in varying degrees of reduction in the inhibition, blocking, lubrication, and filtration loss reduction performance of the final product.
[0021] The second technical solution of the present invention is a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared according to the above preparation method.
[0022] The third technical solution of the present invention is the application of the above-mentioned silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent in drilling fluid.
[0023] The fourth technical solution of the present invention is a water-based drilling fluid comprising the above-mentioned silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent.
[0024] This invention discloses the following technical effects: Existing water-based drilling fluid treatment agents generally suffer from insufficient inhibition, limited plugging effect, poor lubrication, and insufficient stability under high temperature and high salinity conditions when applied to shale formations, making it difficult to meet the drilling requirements of deep and ultra-deep complex shale well sections. This invention provides a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent. By introducing a stable phosphonic acid anchoring layer and a fluorine-free polyionic liquid polymer brush layer on the surface of an inorganic nanocore, combined with a modified starch composite shell, it achieves multi-functional synergy of shale inhibition, micro-nano plugging, lubrication and friction reduction, and filtration loss reduction, significantly improving the application performance of existing water-based drilling fluids in deep shale wells.
[0025] First, the functionalized inorganic nanonuclei (such as ZrP, ZrO2, or UiO-66) used in this invention possess excellent thermal stability and a rigid framework, allowing them to penetrate microfractures and nanopores in the formation under pressure differential, forming a physical sealing framework that effectively mitigates wellbore seepage and shale spalling. Simultaneously, the nucleus particles are anchored on the surface by phosphonic acid molecules, forming stable Zr–O–P bonds, avoiding the defects of traditional silane coupling layers that are prone to hydrolysis and failure under high temperature and high salinity environments. Thus, at the pore scale, it possesses a dual sealing mechanism of "size sieving + interface bridging," constructing a "rigid-flexible synergistic" micro-nano sealing network; the anti-hydrolysis / anti-salting properties of the Zr–O–P bonds further prevent interface delamination, significantly improving the durability of the sealing layer.
[0026] Secondly, this invention constructs a fluorine-free polyionic liquid polymer brush layer to form a dense polymer layer with quaternary ammonium cations on the core surface. This brush layer not only competes with interlayer water in the clay of shale, inhibiting clay hydration swelling and dispersion, but also enhances adsorption and film densification on surfaces containing organic matter / clay by using quaternary ammonium cations as the main component and supplemented by heterocyclic cations (such as pyridinium / imidazolium). Simultaneously, it can form a low-friction directional adsorption film on the wellbore and drill string metal surfaces, significantly reducing friction and torque. Specifically, N-vinylpyrrolidone and polyethylene glycol methacrylate construct a thick hydration layer and a compliant brush layer, forming a dual mechanism of "hydration lubrication / boundary lubrication," significantly reducing interfacial shear; lauryl methacrylate forms comb-shaped side chains providing point-like hydrophobic anchoring and anti-shear migration capabilities, improving the durability and self-healing of the lubricating film; 2-acrylamide-2-methylpropanesulfonic acid provides charge retention and framework stability under high ionic strength, while N-vinylpyrrolidone further enhances thermal stability. Furthermore, the fluorine-free anions (such as lactate, acetate, or methanesulfonate) used in this invention avoid the hydrolytic corrosion, hydrofluoric acid release, and environmental risks associated with common fluorine-containing ionic liquids, thereby improving the safety and environmental friendliness of the system without sacrificing inhibition and lubrication performance.
[0027] Furthermore, this invention introduces a modified starch composite layer into the filter cake shell. Utilizing the flexible segments and hydrophilic groups of the modified starch molecules, this layer further fills the filter cake pores and synergizes with the polyionic liquid polymer brush layer. This composite shell enhances the density and integrity of the filter cake, thus reducing filtration loss. Simultaneously, its flexible segments can accumulate and overlap on the formation surface, forming a lubrication and buffer layer, further improving lubrication and reducing mechanical wear between the drill bit and the wellbore.
[0028] In summary, the core-shell gradient composite structure of the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent of this invention achieves a multifunctional synergistic effect: the inorganic core provides rigid support and micro / nano-level plugging, the polyionic liquid polymer brush layer imparts strong shale inhibition and lubrication properties, and the grafted modified starch composite layer improves filter cake density and filtration loss reduction. The covalently stable core-shell interface, the thick hydrated brush layer structure, and the comb-shaped stable film characteristics jointly ensure the maintenance of function under high temperature, high salinity, strong shear, and multi-cycle conditions. The organic combination of these three elements allows the material to maintain stable dispersion at 220℃ and in high-concentration brine environments, without flocculation or failure. Experimental results show that the water-based drilling fluid treated with this invention, after hot rolling at 220℃ for 24 hours, still exhibits a shale expansion rate of <8%, a rolling recovery rate of >99%, an API filtration loss of <3.5 mL, an HTHP filtration loss of <15.0 mL, and a cake permeability of ≤2.00×10⁻⁶. -3 It boasts excellent performance with a lubrication coefficient ≤0.08 and a mD. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 The particle size distribution diagram is shown for the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in Example 1.
[0031] Figure 2 The particle size distribution diagram is shown for the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in Example 2.
[0032] Figure 3 The particle size distribution diagram is shown for the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in Example 3.
[0033] Figure 4 The particle size distribution diagram is shown for the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in Example 4. Detailed Implementation
[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0035] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0036] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.
[0037] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This specification and embodiments are merely exemplary.
[0038] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0039] Unless otherwise specified, the term "parts" in this invention refers to parts by mass.
[0040] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0041] Unless otherwise specified, the technical solutions described in this invention are all conventional solutions in the field, and the reagents or raw materials used are all purchased from commercial channels or are publicly available unless otherwise specified.
[0042] Example 1
[0043] This embodiment provides a method for preparing a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, the steps of which are as follows: Step 1: Take 100 parts of deionized water and add it to a polytetrafluoroethylene beaker, place it on a magnetic heating stirrer, heat it to 50°C, add 5 parts of nanonuclei, and ultrasonically disperse for 10 min to obtain a uniform dispersion; then slowly add 0.5 parts of anchoring agent, adjust the pH to 3.0 with dilute phosphoric acid under stirring conditions, and heat it to 65°C, and continue stirring for 2 h; after the reaction is completed, centrifuge (8000 rpm, 10 min) and wash three times with deionized water to obtain a nano slurry with an anchoring layer on the surface (dispersed with deionized water, with the solid content controlled at 1 wt%), as intermediate product I.
[0044] Step 2: Add 100 parts of deionized water and polymerizable ionic liquid monomer to a three-necked flask to a concentration of 0.8 mol / L. Heat to 25°C and stir to dissolve, obtaining a monomer solution. Then, prepare a fluoride-free anionic salt solution (0.8 mol / L, deionized water) at a constant temperature of 25°C. Under stirring, slowly add the fluoride-free anionic salt solution dropwise to the monomer solution, maintaining a molar ratio of fluoride-free anionic salt to monomer cations of 1.05:1. Continue the reaction for 2 hours, maintaining the system pH at 6.0 and controlling the temperature not to exceed 40°C. After the reaction, send the reaction solution to a nanofiltration / tangential flow filtration (NF / TFF) system for displacement washing: the displacement solution is a water / ethanol mixture (ethanol volume fraction 10%); operating temperature 20°C; transmembrane pressure difference 2 bar; tangential linear velocity 0.8 m / s; the displacement solution is continuously added using a constant volume displacement washing method until Cl... - The content is 0.01 wt%. The retained liquid is collected to obtain a fluorine-free polymerizable ionic liquid monomer solution, which is used as intermediate product II.
[0045] Step 3: In a four-necked flask, add 90 parts deionized water and 10 parts ethanol as solvents. Then, sequentially add 40 parts intermediate product II, 10 parts 2-acrylamido-2-methylpropanesulfonic acid, 8 parts N-vinylpyrrolidone, 4 parts polyethylene glycol methacrylate (number average molecular weight 500), 0.8 parts lauryl methacrylate, and 0.05 parts N-hydroxymethylacrylamide. Stir for 20 min to obtain a monomer mixture. Then, slowly add 10 parts intermediate product I under stirring and ultrasonically disperse for 10 min. After purging with nitrogen for 20 min, raise the temperature to 60℃. Under stirring, add 0.3 parts potassium persulfate and 0.05 parts sodium bisulfite as an initiator system, and polymerize for 4 h. After 3 h of reaction, slowly add 1 part modified starch solution (concentration 20 g / L, solvent: deionized water), and continue the reaction at 60℃ for 1 h to complete the grafting composite. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed three times to obtain a dispersion, which is then spray-dried to obtain a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent.
[0046] In step one, the nanonucleus is zirconium phosphate nanoparticles with an average particle size of 50 nm.
[0047] In step one, the anchoring agent is vinylphosphonic acid.
[0048] In step two, the polymeric ionic liquid monomers are a combination of methacryloyloxyethyltrimethylammonium chloride, N-vinylpyridine chloride, and 1-vinyl-3-methylimidazolium chloride. The molar ratio of methacryloyloxyethyltrimethylammonium chloride to N-vinylpyridine chloride to 1-vinyl-3-methylimidazolium chloride is 60:20:20.
[0049] In step two, the fluorine-free anionic salt is sodium lactate.
[0050] In step three, the modified starch is hydroxyethyl starch.
[0051] The particle size distribution of the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in this embodiment is as follows: Figure 1 As shown, the average particle size is 232 nm.
[0052] Example 2
[0053] This embodiment provides a method for preparing a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, the steps of which are as follows: Step 1: Take 100 parts of deionized water and add it to a polytetrafluoroethylene beaker, place it on a magnetic heating stirrer, heat it to 55°C, add 7.5 parts of nanonuclei, and ultrasonically disperse for 12.5 min to obtain a uniform dispersion; then slowly add 1 part of anchoring agent, adjust the pH to 3.5 with dilute phosphoric acid under stirring conditions, and heat it to 70°C, and continue stirring for 3 h; after the reaction is completed, centrifuge (8000 rpm, 10 min) and wash three times with deionized water to obtain a nano slurry with an anchoring layer on the surface (dispersed with deionized water, with the solid content controlled at 2 wt%), as intermediate product I.
[0054] Step 2: Add 100 parts of deionized water and polymerizable ionic liquid monomer to a three-necked flask to a concentration of 0.9 mol / L. Heat to 30°C and stir to dissolve, obtaining a monomer solution. Then, prepare a fluoride-free anionic salt solution (0.9 mol / L, deionized water) at a constant temperature of 30°C. Under stirring, slowly add the fluoride-free anionic salt solution dropwise to the monomer solution, maintaining a molar ratio of fluoride-free anionic salt to monomer cations of 1.12:1. Continue the reaction for 3 hours, maintaining the system pH at 6.7 and controlling the temperature not to exceed 40°C. After the reaction, send the reaction solution to a nanofiltration / tangential flow filtration (NF / TFF) system for displacement washing: the displacement solution is a water / ethanol mixture (ethanol volume fraction 15%); operating temperature 25°C; transmembrane pressure difference 4 bar; tangential linear velocity 1.1 m / s; the displacement solution is continuously added using a constant volume displacement washing method until Cl... - The content is 0.03 wt%. The retained solution is collected to obtain a fluorine-free polymerizable ionic liquid monomer solution, which is used as intermediate product II.
[0055] Step 3: In a four-necked flask, add 92 parts deionized water and 8 parts ethanol as solvents. Then, sequentially add 55 parts intermediate product II, 15 parts 2-acrylamido-2-methylpropanesulfonic acid, 11 parts N-vinylpyrrolidone, 6 parts polyethylene glycol methacrylate (number average molecular weight 1000), 1.1 parts lauryl methacrylate, and 0.12 parts N-hydroxymethylacrylamide. Stir for 25 min to obtain a monomer mixture. Then, slowly add 20 parts intermediate product I under stirring and ultrasonically disperse for 10 min. After purging with nitrogen for 25 min, raise the temperature to 65℃ and add 0.45 parts potassium persulfate and 0.1 parts sodium bisulfite as an initiator under stirring. The polymerization reaction is carried out for 5 h. After 3.5 h of reaction, slowly add 2.5 parts modified starch solution (concentration 12 g / L, solvent: deionized water), and continue the reaction at 65℃ for 1.5 h to complete the grafting composite. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed three times to obtain a dispersion, which is then spray-dried to obtain a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent.
[0056] In step one, the nanonucleus is nano-zirconia with an average particle size of 75 nm.
[0057] In step one, the anchoring agent is allylphosphonic acid.
[0058] In step two, the polymeric ionic liquid monomers are a combination of methacryloyloxyethyltrimethylammonium chloride, N-vinylpyridine chloride, and 1-vinyl-3-methylimidazolium chloride. The molar ratio of methacryloyloxyethyltrimethylammonium chloride to N-vinylpyridine chloride to 1-vinyl-3-methylimidazolium chloride is 65:17.5:17.5.
[0059] In step two, the fluorine-free anionic salt is sodium acetate.
[0060] In step three, the modified starch is hydroxypropyl starch.
[0061] The particle size distribution of the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in this embodiment is as follows: Figure 2 As shown, the average particle size is 270 nm.
[0062] Example 3
[0063] This embodiment provides a method for preparing a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, the steps of which are as follows: Step 1: Take 100 parts of deionized water and add it to a polytetrafluoroethylene beaker, place it on a magnetic heating stirrer, heat it to 60°C, add 10 parts of nanonuclei, and ultrasonically disperse for 15 min to obtain a uniform dispersion; then slowly add 1.5 parts of anchoring agent, adjust the pH to 4.0 with dilute phosphoric acid under stirring conditions, and heat it to 75°C, and continue stirring for 4 h; after the reaction is completed, centrifuge (8000 rpm, 10 min) and wash three times with deionized water to obtain a nano slurry with an anchoring layer on the surface (dispersed with deionized water, with the solid content controlled at 3 wt%), as intermediate product I.
[0064] Step 2: Add 100 parts of deionized water and polymerizable ionic liquid monomer to a three-necked flask to a concentration of 1.0 mol / L. Heat to 35°C and stir to dissolve, obtaining a monomer solution. Then, prepare a fluorine-free anionic salt solution (concentration 1.0 mol / L, solvent: deionized water) at a constant temperature of 35°C. Under stirring, slowly add the fluorine-free anionic salt solution dropwise to the monomer solution above, maintaining the molar ratio of fluorine-free anionic salt to monomer cation at 1.20:1. Continue the reaction for 4 hours, maintaining the pH of the system at 7.5 and controlling the temperature not to exceed 40°C. After the reaction was completed, the above reaction solution was sent to a nanofiltration / tangential flow filtration (NF / TFF) system for displacement washing: the displacement solution was a water / ethanol mixture (ethanol volume fraction of 20%); the operating temperature was 30℃; the transmembrane pressure difference was 6 bar; the tangential linear velocity was 1.5 m / s; the displacement solution was continuously added using a constant volume displacement washing method until the Cl- content was 0.05 wt%, and the retained solution was collected to obtain a fluorine-free polycrystalline ionic liquid monomer solution, which was used as intermediate product II.
[0065] Step 3: In a four-necked flask, add 95 parts deionized water and 5 parts ethanol as solvents. Then, sequentially add 70 parts intermediate product II, 20 parts 2-acrylamido-2-methylpropanesulfonic acid, 15 parts N-vinylpyrrolidone, 8 parts polyethylene glycol methacrylate (number average molecular weight 1500), 1.5 parts lauryl methacrylate, and 0.2 parts N-hydroxymethylacrylamide. Stir for 30 min to obtain a monomer mixture. Then, slowly add 30 parts intermediate product I under stirring and ultrasonically disperse for 10 min. After purging with nitrogen for 30 min, raise the temperature to 70℃. Under stirring, add 0.6 parts potassium persulfate and 0.15 parts sodium bisulfite as an initiator system, and polymerize for 6 h. At 4 h of reaction, slowly add 5 parts modified starch solution (concentration 5 g / L, solvent: deionized water), and continue the reaction at 70℃ for 2 h to complete the grafting composite. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed three times to obtain a dispersion, which is then spray-dried to obtain a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent.
[0066] In step one, the nanonucleus is UiO-66 (Zr) with an average particle size of 100 nm.
[0067] In step one, the anchoring agent is 2-methacryloyloxyethylphosphonic acid.
[0068] In step two, the polymeric ionic liquid monomers are a combination of methacryloyloxyethyltrimethylammonium chloride, N-vinylpyridine chloride, and 1-vinyl-3-methylimidazolium chloride. The molar ratio of methacryloyloxyethyltrimethylammonium chloride to N-vinylpyridine chloride to 1-vinyl-3-methylimidazolium chloride is 70:15:15.
[0069] In step two, the fluorine-free anionic salt is sodium methanesulfonate.
[0070] In step three, the modified starch is starch hydroxypropyltrimethylammonium chloride.
[0071] The particle size distribution of the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in this embodiment is as follows: Figure 3 As shown, the average particle size is 302 nm.
[0072] Example 4
[0073] This embodiment provides a method for preparing a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, the steps of which are as follows: Step 1: Take 100 parts of deionized water and add it to a polytetrafluoroethylene beaker, place it on a magnetic heating stirrer, heat it to 55°C, add 8 parts of nanonuclei, and ultrasonically disperse for 15 min to obtain a uniform dispersion; then slowly add 1.5 parts of anchoring agent, adjust the pH to 4.0 with dilute phosphoric acid under stirring conditions, and heat it to 65°C, and continue stirring for 3 h; after the reaction is completed, centrifuge (8000 rpm, 10 min), wash with deionized water 3-4 times to obtain a nano slurry with an anchoring layer on the surface (dispersed with deionized water, with the solid content controlled at 3 wt%), as intermediate product I.
[0074] Step 2: Add 100 parts of deionized water and polymerizable ionic liquid monomer to a three-necked flask to a concentration of 1.0 mol / L. Heat to 30°C and stir to dissolve, obtaining a monomer solution. Then, prepare a fluoride-free anionic salt solution (concentration 1.0 mol / L, solvent: deionized water) at a constant temperature of 30°C. Under stirring, slowly add the fluoride-free anionic salt solution dropwise to the monomer solution, maintaining a molar ratio of fluoride-free anionic salt to monomer cations of 1.10:1. Continue the reaction for 3.5 h, maintaining the system pH at 7.0 and controlling the temperature not to exceed 40°C. After the reaction, send the reaction solution to a nanofiltration / tangential flow filtration (NF / TFF) system for displacement washing: the displacement solution is a water / ethanol mixture (ethanol volume fraction 16%); operating temperature 25°C; transmembrane pressure difference 5 bar; tangential linear velocity 1.0 m / s; the displacement solution is continuously added using a constant volume displacement washing method until Cl... - The content is 0.02 wt%. The retained solution is collected to obtain a fluorine-free polymorphic ionic liquid monomer solution, which is used as intermediate product II.
[0075] Step 3: In a four-necked flask, add 90 parts deionized water and 10 parts ethanol as solvents. Then, sequentially add 60 parts intermediate product II, 20 parts 2-acrylamido-2-methylpropanesulfonic acid, 10 parts N-vinylpyrrolidone, 8 parts polyethylene glycol methacrylate (number average molecular weight 1200), 1.0 part lauryl methacrylate, and 0.06 parts N-hydroxymethylacrylamide. Stir for 30 min to obtain a monomer mixture. Subsequently, slowly add 25 parts intermediate product I under stirring and ultrasonically disperse for 10 min. After purging with nitrogen for 30 min, raise the temperature to 66℃. Under stirring, add 0.5 parts potassium persulfate and 0.08 parts sodium bisulfite as an initiator system, and polymerize for 5.5 h. After 4 h of reaction, slowly add 3 parts modified starch solution (concentration 15 g / L, solvent: deionized water), and continue the reaction at 67℃ for 1.5 h to complete the grafting composite. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed three times to obtain a dispersion, which is then spray-dried to obtain a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent.
[0076] In step one, the nanonucleus consists of 40 parts of nano-zirconium phosphate, 30 parts of nano-zirconium oxide, and 30 parts of UiO-66 (Zr) with an average particle size of 68 nm, based on a mass fraction of 100.
[0077] In step one, the anchoring agent consists of 35 parts vinylphosphonic acid, 30 parts allylphosphonic acid and 35 parts 2-methacryloyloxyethylphosphonic acid, with a mass ratio of 100.
[0078] In step two, the polymeric ionic liquid monomers are a combination of methacryloyloxyethyltrimethylammonium chloride, N-vinylpyridine chloride, and 1-vinyl-3-methylimidazolium chloride. The molar ratio of methacryloyloxyethyltrimethylammonium chloride to N-vinylpyridine chloride to 1-vinyl-3-methylimidazolium chloride is 65:20:15.
[0079] In step two, the fluoride-free anionic salt is a combination of sodium lactate, sodium acetate, and sodium methanesulfonate. The molar ratio of sodium lactate, sodium acetate, and sodium methanesulfonate is 20:30:50.
[0080] In step three, the modified starch is starch hydroxypropyltrimethylammonium chloride.
[0081] The particle size distribution of the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared in this embodiment is as follows: Figure 4 As shown, the average particle size is 262 nm.
[0082] Comparative Example 1: (Silane Substitution)
[0083] The only difference from Example 4 is that the anchoring agent in step one is replaced with vinyltriethoxysilane; the remaining steps and parameters are the same as in Example 4.
[0084] Comparative Example 2: (Without quaternary ammonium salt, inhibition comparison)
[0085] The only difference from Example 4 is that in step two, the polymerizable ionic liquid monomer is a mixture of N-vinylpyridine chloride and 1-vinyl-3-methylimidazolium chloride in a molar ratio of 50:50; the remaining steps and parameters are the same as in Example 4.
[0086] Comparative Example 3: (No nanonucleus, blocking performance comparison)
[0087] The only difference from Example 4 is that step one is deleted, and intermediate product I in the reactants of step three is removed accordingly; the remaining steps and parameters are the same as in Example 4.
[0088] Comparative Example 4: (No hydrophobic long chains, compared to lubrication)
[0089] The only difference from Example 4 is that the addition of polyethylene glycol methacrylate and lauryl methacrylate in step three is omitted; the remaining steps and parameters are the same as in Example 4.
[0090] Comparative Example 5: (Unmodified starch, compared to reduced filtration loss)
[0091] The only difference from Example 4 is that the addition of modified starch in step three is omitted; all other steps and parameters are the same as in Example 4.
[0092] Comparative Example 6: (without temperature- and salt-resistant monomers)
[0093] The only difference from Example 4 is that the addition of 2-acrylamide-2-methylpropanesulfonic acid and N-vinylpyrrolidone in step three is omitted; the remaining steps and parameters are the same as in Example 4.
[0094] The silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agents obtained in the above examples and comparative examples were added to the following drilling fluids for performance evaluation. The performance tests were conducted according to the test methods in GB / T 16783.1-2014 "Field Testing of Drilling Fluids for Petroleum and Natural Gas Industry - Part 1: Water-based Drilling Fluids", GB / T 29170-2012 "Laboratory Testing of Drilling Fluids for Petroleum and Natural Gas Industry", and SY / T 6094-1994 "Evaluation Procedures for Lubricants for Drilling Fluids". The results are as follows.
[0095] Drilling fluid formulation: Fresh water + 1.5% bentonite + 0.5% sodium hydroxide + 3% modified lignite resin + 3% sulfonated asphalt + 5% potassium chloride + 15% sodium chloride + 1% high-temperature viscosifier + barite, weighted to a density of 2.0 g / cm³. 3 (The percentage in the formula refers to the percentage of fresh water by mass).
[0096] Table 1. Effects of silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agents on drilling fluid rheology and temperature and salt resistance. Blank drilling fluid 220 0 48 38 10 8 7 24 36 32 4 3 2 2% Example 1 220 0 49.5 39 10.5 8 7 24 48.5 39 9.5 7.5 7 2% Example 2 220 0 50 39 11 8 7 24 49.5 39 10.5 8 7 2% Example 3 220 0 51 40 11 8 7 24 50 40 10 8 7 2% Example 4 220 0 49 39 10 8 7 24 47.5 38 9.5 7.5 7 2% Comparative Example 1 220 0 51 40 11 8 7 24 43 36 7 5 4 2% Comparative Example 2 220 0 50.5 40 10.5 8 7 24 49 39 10 8 7 2% Comparative Example 3 220 0 49.5 39 10.5 8 7 24 50 40 10 8 7 2% Comparative Example 4 220 0 48.5 38 10.5 8 7 24 47.5 38 9.5 7.5 7 2% vs. 5 220 0 49 39 10 8 7 24 48 39 9 7 6 2% vs. 6 220 0 48.5 39 9.5 7.5 7 24 39 34 5 4 3
[0097] Table 2. Effects of silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agents on drilling fluid plugging and filtration reduction performance. Blank drilling fluid 8.1 35.2 5.3 9.47 2% Example 1 3.2 14.6 2.7 2.00 2% Example 2 3.0 14.2 2.5 1.80 2% Example 3 2.6 13.4 2.2 1.50 2% Example 4 2.9 13.8 2.4 1.68 2% Comparative Example 1 5.3 26.8 4.1 5.58 2% Comparative Example 2 3.0 14.0 2.5 1.78 2% Comparative Example 3 6.0 29.2 4.5 6.67 2% Comparative Example 4 3.1 14.6 2.8 2.07 2% vs. 5 5.8 28.0 2.6 3.69 2% vs. 6 6.9 31.8 4.8 7.74
[0098] Table 3. Effects of silane-free polyionic liquid functionalized nanocomposite drilling fluid pretreatment agents on the lubrication and inhibition properties of drilling fluids. Blank drilling fluid 0.2769 0.3011 1.130 71.8 30.2 2% Example 1 0.0773 72.09 0.0793 73.67 0.528 99.1 6.6 2% Example 2 0.0739 73.30 0.0771 74.39 0.479 99.6 6.1 2% Example 3 0.0718 74.05 0.0743 75.34 0.435 99.9 5.3 2% Example 4 0.0721 73.95 0.0750 75.09 0.445 99.8 5.7 2% Comparative Example 1 0.0874 68.42 0.0912 69.71 0.640 99.2 6.0 2% Comparative Example 2 0.0729 73.68 0.0767 74.53 0.472 85.3 15.8 2% Comparative Example 3 0.0744 73.14 0.0875 70.94 0.666 99.5 5.9 2% Comparative Example 4 0.1133 59.06 0.1189 60.51 0.721 97.7 6.3 2% vs. 5 0.0777 71.93 0.0796 73.56 0.549 98.6 5.8 2% vs. 6 0.1651 40.35 0.1704 43.41 0.909 80.1 19.7
[0099] Note: T: Aging temperature of base slurry or drilling fluid, °C.
[0100] t: Drilling fluid aging time, h.
[0101] AV: Apparent viscosity of drilling fluid, mPa·s.
[0102] PV: Drilling fluid plastic viscosity, mPa·s.
[0103] YP: Drilling fluid dynamic shear force, Pa.
[0104] φ6: The dial reading when the rotational viscometer rotates at 6 rpm, dimensionless.
[0105] φ3: The dial reading when the rotational viscometer rotates at 3 rpm, dimensionless.
[0106] API: Pressure loss in drilling fluid (0.7 MPa, room temperature, 30 min), mL.
[0107] HTHP: Drilling fluid high-temperature and high-pressure filtration loss (3.5MPa, 180℃, 30min), mL.
[0108] δ: HTHP cake thickness, mm.
[0109] θ: HTHP cake permeability, ×10 -3 mD.
[0110] CF EP EP: Extreme pressure lubrication coefficient, dimensionless.
[0111] ΔCF EP : EP extreme pressure lubrication coefficient reduction rate,%.
[0112] CF FB : Coefficient of friction of four balls (147N, 120rpm, 30min), dimensionless.
[0113] ΔCF FB: Reduction rate of friction coefficient of four balls,%.
[0114] D: Diameter of four-ball wear scar, mm.
[0115] η: Rolling recovery rate, %.
[0116] γ: linear expansion rate, %.
[0117] As shown in Table 1, the blank drilling fluid and the data from Examples 1-4 indicate that the 2% silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent has virtually no effect on the rheological properties of the drilling fluid before aging, but significantly improves its rheological properties after high-temperature aging (the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent of this invention can reduce the rate of decline in rheological parameters of the drilling fluid during high-temperature aging, allowing the system to maintain good viscosity-shear level, low-shear structure, and suspension capacity after high temperature, thus demonstrating better temperature and salt resistance stability). This indicates that the treatment agent can significantly improve the temperature and salt resistance of the drilling fluid. As shown in the corresponding data in Table 2, the 2% silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent significantly improves the plugging and filtration loss reduction performance of the drilling fluid, specifically with maximum reduction rates of 67.90%, 61.93%, 58.49%, and 84.16% for API filtration loss, HTHP filtration loss, HTHP cake thickness, and HTHP cake permeability, respectively. As shown in Table 3, the 2% silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent significantly improved the lubrication, friction reduction, and inhibition performance of the drilling fluid. Specifically, the maximum reduction rates of the EP extreme pressure lubrication coefficient, four-ball friction coefficient, and four-ball wear scar diameter were 74.05%, 75.34%, and 61.50%, respectively; the maximum increase in rolling recovery rate was 28.1%; and the maximum reduction in linear expansion rate was 24.9%. These results fully demonstrate that the silane-free polyionic liquid multifunctional nanocomposite treatment agent provided by this invention achieves a synergistic effect of inhibition, plugging, and lubrication simultaneously under high temperature and high salt conditions.
[0118] As can be seen from the data in Examples 4 and Comparative Example 1 in Tables 1-3, replacing the anchoring agent in step one with a silane coupling agent will lead to a decrease in the stability of the treatment agent at a high temperature of 220°C, resulting in phenomena such as decreased viscosity and shear rate, increased filtration loss, increased mud cake permeability, and decreased lubrication performance after drilling fluid aging.
[0119] As can be seen from the data of Example 4 and Comparative Example 2 in Tables 1-3, removing methacryloyloxyethyltrimethylammonium chloride in step 2 and retaining only N-vinylpyridine chloride and 1-vinyl-3-methylimidazolium chloride will result in a significant decrease in the inhibitory performance of the treatment agent, which in turn leads to a decrease in the rolling recovery rate and an increase in the linear expansion rate after drilling fluid aging.
[0120] As can be seen from the data in Examples 4 and Comparative Example 3 in Tables 1-3, if nano-cores are not added during the synthesis process, the plugging and filtration loss reduction performance of the treatment agent will decrease, which is manifested as an increase in the filtration loss of drilling fluid and the permeability of mud cake after aging.
[0121] As can be seen from the data of Example 4 and Comparative Example 4 in Tables 1-3, if polyethylene glycol methacrylate and lauryl methacrylate are not added during the synthesis process, the lubrication and friction reduction performance of the treatment agent will decrease. This is manifested in a significant increase in the EP extreme pressure lubrication coefficient, four-ball friction coefficient and four-ball wear scar diameter of the drilling fluid after aging, and a slight decrease in the coating inhibition, which leads to a slight decrease in the rolling recovery rate.
[0122] As can be seen from the data of Example 4 and Comparative Example 5 in Tables 1-3, if modified starch is not added during the synthesis process, the filtration loss reduction performance of the treatment agent will decrease, which is manifested as an increase in drilling fluid filtration loss and mud cake permeability after aging. It will also reduce the contribution to lubrication improvement, resulting in a slight increase in EP extreme pressure lubrication coefficient, four-ball friction coefficient and four-ball wear scar diameter.
[0123] As can be seen from the data in Examples 4 and Comparative Example 6 in Tables 1-3, if 2-acrylamide-2-methylpropanesulfonic acid and N-vinylpyrrolidone are not added during the synthesis process, the temperature and salt resistance of the treatment agent will be greatly weakened. This will result in a significant decrease in the overall performance of the drilling fluid after aging. Specifically, the aging drilling fluid will exhibit problems such as decreased viscosity and shear rate, increased filtration loss, increased mud cake permeability, increased EP extreme pressure lubrication coefficient, increased four-ball friction coefficient, increased four-ball wear scar diameter, decreased rolling recovery rate, and increased linear expansion rate.
[0124] The silane-free polyionic liquid multifunctional nanocomposite drilling fluid treatment agent proposed in this invention is synergistically constructed from a functionalized inorganic nanocore, a phosphonic acid anchoring layer, a fluorine-free polyionic liquid polymer brush layer, and a modified starch composite layer. Each component plays a specific role and complements the others in the system: the inorganic core provides rigid support and micro / nano-sealing; the phosphonic acid anchoring layer ensures the stability of the core-shell interface; the polyionic liquid brush layer imparts shale inhibition and lubrication properties; lauryl methacrylate and polyethylene glycol methacrylate together provide a stable and durable lubricating film; 2-acrylamide-2-methylpropanesulfonic acid and N-vinylpyrrolidone ensure temperature and salt resistance; and the modified starch flexible segments enhance the filter cake density and reduce filtration loss.
[0125] In this invention, the absence of any one of the raw materials will lead to varying degrees of performance degradation: the absence of quaternary ammonium salt results in insufficient inhibition; the absence of nanonuclei leads to incomplete sealing; the absence of lauryl methacrylate and polyethylene glycol methacrylate leads to unstable lubricating film; the absence of modified starch leads to a significant increase in filtration loss; the absence of 2-acrylamido-2-methylpropanesulfonic acid or N-vinylpyrrolidone leads to a significant decrease in temperature and salt resistance; and the use of silane coupling instead of phosphonic acid anchoring results in interfacial instability and difficulty in maintaining stability in high-temperature and high-salt environments. Therefore, all components of this invention are indispensable; only through overall synergistic action can excellent comprehensive performance in shale inhibition, sealing, lubrication, filtration loss reduction, and temperature and salt resistance be achieved.
[0126] In this invention, the starch used is not ordinary native starch, but modified starch, specifically hydroxyethyl starch, hydroxypropyl starch, or starch hydroxypropyltrimethylammonium chloride. This type of modified starch, by introducing hydroxyethyl, hydroxypropyl, or cationic quaternary ammonium groups, weakens the strong hydrogen bonds and regular crystalline structure between native starch molecules, thereby improving its water dispersibility, flexibility, and compatibility with the polymer shell. Therefore, in the system of this invention, the modified starch does not exist alone in the form of free starch particles, but is added in the later stages of the polymerization reaction and grafted together with the polyionic liquid polymer brush layer to form a composite shell structure.
[0127] From the perspective of thermal conditions, in the preparation process of this invention, the modified starch is added 3-4 hours after the polymerization reaction, at a reaction temperature of 60-70℃. This temperature is far below the temperature required for starch to undergo thermal decomposition or carbonization, therefore carbonization will not occur during the preparation process. Although the product undergoes high-temperature aging conditions after being applied to drilling fluid, the modified starch has been coated, entangled, or grafted into the polyionic liquid composite shell and is synergistically protected by temperature-resistant and salt-resistant segments such as AMPS and NVP, as well as the rigid framework of inorganic nanonuclei. Its working environment is an aqueous drilling fluid system, not a carbonization environment under dry, oxygen-deficient, or high-temperature burning conditions. Therefore, the modified starch in this invention is mainly likely to undergo limited thermal degradation or structural relaxation, rather than carbonization in the conventional sense.
[0128] From the perspective of filtration loss reduction mechanism, modified starch mainly functions through the following mechanisms: First, modified starch molecules possess a large number of hydroxyl groups, ether bonds, and cationic groups, enabling them to form hydration segments in water-based drilling fluids, increasing the hydrophilic flexible layer on the filter cake surface. Second, the flexible segments of modified starch can form hydrogen bonds, electrostatic interactions, and chain entanglement with polyionic liquid brush layers, N-vinylpyrrolidone segments, and polyethylene glycol side chains, thereby improving the continuity and film-forming ability of the composite shell. Third, modified starch segments can fill the micropores between bentonite particles, weighting material particles, and nano-plugging particles, improving the particle size distribution of the filter cake and making it denser and more complete. Fourth, the modified starch composite layer synergizes with the rigid plugging effect of the inorganic nanocore; the former provides flexible filling and film formation, while the latter provides physical support and bridging for micro- and nano-pore throats, thereby jointly reducing the seepage channels of filtrate through the filter cake and micro-cracks.
[0129] The experimental results of this invention also support the above mechanism. Compared with Example 4, Comparative Example 5 only omitted the modified starch, while keeping the other components and process conditions the same. The results showed that the API filtration loss and HTHP filtration loss of Comparative Example 5 were significantly higher than those of Example 4, indicating that the addition of modified starch can effectively improve the filter cake density and reduce filtration loss. At the same time, the filter cake permeability of Comparative Example 5 was also higher than that of Example 4, indicating that the modified starch composite layer directly contributes to reducing filter cake permeability. It can be seen that the role of modified starch in this invention does not rely on the high-temperature stability of single starch, but achieves filtration loss reduction through a synergistic mechanism of "modified starch flexible filling film formation, polyionic liquid shell adsorption coating, and inorganic nano-core micro-nano sealing".
[0130] Therefore, the modified starch in this invention does not carbonize during preparation, and in application, it does not rely solely on ordinary starch to withstand high temperatures. Instead, it acts as a flexible filtration loss reduction component in the composite shell to construct a dense filter cake. Its filtration loss reduction effect comes from hydration thickening, pore filling, filter cake densification, interfacial adsorption, and synergy with the nano-blocking structure, rather than simply relying on the high-temperature resistance of the starch itself.
[0131] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing a silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent, characterized in that, Includes the following steps: Step 1: Disperse the nanonuclei in water to obtain a dispersion; add an anchoring agent to the dispersion to react and obtain intermediate product I; Step 2: Add the fluorine-free anionic salt solution to the monomer solution to carry out the reaction, followed by displacement washing to obtain intermediate product II; Step 3: Add intermediate product II, 2-acrylamide-2-methylpropanesulfonic acid, N-vinylpyrrolidone, polyethylene glycol methacrylate, lauryl methacrylate, and N-hydroxymethylacrylamide to the mixed solvent and mix well to obtain a monomer mixture; add intermediate product I to the monomer mixture, disperse evenly, and remove oxygen; then heat to 60-70℃ and add an initiator system to carry out a polymerization reaction; during the polymerization reaction, add modified starch solution for grafting and composite; after the polymerization reaction is completed, centrifuge and wash, and then spray dry to obtain the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent; In step one, the nanocore is at least one of nano-zirconium phosphate, nano-zirconium oxide, and UiO-66; the anchoring agent is at least one of vinylphosphonic acid, allylphosphonic acid, and 2-methacryloyloxyethylphosphonic acid. In step two, the monomer solution is prepared by dissolving the polymerizable ionic liquid monomer in water; the polymerizable ionic liquid monomer is a mixture of methacryloyloxyethyltrimethylammonium chloride, N-vinylpyridine chloride and 1-vinyl-3-methylimidazolium chloride in a molar ratio of (60-70):(15-20):(15-20); The mixed solvent is a mixture of water and ethanol in a mass ratio of (90~95):(5~10).
2. The preparation method according to claim 1, characterized in that, In step one, the mass fraction of nanonuclei in the dispersion is 5%~10%; the mass ratio of nanonuclei to anchoring agent is (5~10):(0.5-1.5); the temperature of the dispersion is 50~60℃; the reaction conditions are set as follows: pH 3.0~4.0, reaction temperature 65~75℃, and reaction time 2~4h.
3. The preparation method according to claim 1, characterized in that, The nanonucleus has a particle size of 50~100nm; in step one, after the reaction is completed, the steps of centrifugation, washing, and dispersion with water to a solid content of 1wt%~3wt% are also included.
4. The preparation method according to claim 1, characterized in that, In step two, the concentration of the fluorine-free anionic salt solution is 0.8~1.0 mol / L; the molar ratio of the fluorine-free anionic salt to the polymerizable ionic liquid monomer is (1.05~1.20):1; the reaction conditions are set as follows: pH 6.0~7.5, reaction temperature not exceeding 40℃, and reaction time 2~4h; the fluorine-free anionic salt is at least one of sodium lactate, sodium acetate, and sodium methanesulfonate.
5. The preparation method according to claim 1, characterized in that, In step three, the amount of intermediate product II added is 40% to 70% of the mass of the mixed solvent, the amount of 2-acrylamide-2-methylpropanesulfonic acid added is 10% to 20% of the mass of the mixed solvent, the amount of N-vinylpyrrolidone added is 8% to 15% of the mass of the mixed solvent, the amount of polyethylene glycol methacrylate added is 4% to 8% of the mass of the mixed solvent, the amount of lauryl methacrylate added is 0.8% to 1.5% of the mass of the mixed solvent, and the amount of N-hydroxymethylacrylamide added is 0.05% to 0.2% of the mass of the mixed solvent; the amount of intermediate product I added is 10% to 30% of the mass of the mixed solvent.
6. The preparation method according to claim 1, characterized in that, The initiation system is a mixture of potassium persulfate and sodium bisulfite in a mass ratio of (0.3~0.6):(0.05~0.15); the amount of the initiation system added is 0.35%~0.75% of the mass of the mixed solvent. The concentration of the modified starch solution is 5~20 g / L, and the modified starch is hydroxyethyl starch, hydroxypropyl starch or starch hydroxypropyltrimethylammonium chloride; the amount of modified starch solution added is 1%~5% of the mass of the mixed solvent.
7. The preparation method according to claim 1, characterized in that, The polymerization reaction conditions are set as follows: reaction temperature 60~70℃, reaction time 4~6h; When the polymerization reaction has been going on for 3-4 hours, a modified starch solution is added for grafting and compounding.
8. A silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent prepared by the preparation method according to any one of claims 1 to 7.
9. The application of the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent as described in claim 8 in drilling fluid.
10. A water-based drilling fluid, characterized in that, It includes the silane-free polyionic liquid functionalized nanocomposite drilling fluid treatment agent as described in claim 8.
Citation Information
Patent Citations
High-strength, low-elasticity and high-density high temperature-resistant cement slurry
CN108439872A
Glass fiber surfaces modified without sizing material and silane, composite materials produced therefrom, and method for producing the modified glass fiber surfaces
CN110753678A